(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
High-fiber composite noodles were made from the combination of wheat, tiger nut residue and cassava flour blends. High fiber inclusion (up to 20 %) was achieved presenting an excellent option for formulating healthier noodles. The cooking quality and fasting blood glucose of the noodles were evaluated and the data generated were subjected to analysis of variance (ANOVA) and means were separated using Duncan multiple range test (DMRT) to establish the significant difference (p <0.05). Available carbohydrate, glycemic index and load were also determined. The result of the cooking quality of the noodles generated include; cooking time (38–40 min.), cooking loss (0.22–0.82 g), water uptake (0.14–0.17 %), and bulk density (0.26–0.53 g/ml). Fasting blood glucose (85.85–110.37 mg/dL), glycemic index (36.14–49.17), glycemic load (9.36–14.93) and available carbohydrate (25.90–30.37 g/100g) values for noodles remained lower than wheat controls, confirming reduced postprandial glycemic response and overall functional suitability. The composite noodles performed favourably when compared with the control (100 % wheat flour).